D4N2024 Presentation Showcase – Thematic Session 1a: Agriculture and food security & nutrition pathways - Khanam, Taznoore Samina; Singh, Tushar; Kumar, Shalander; Uddin, Md Amin; Burrone; Sara; Scognamillo, A.; Poudel, D.; Rub, A.; Song, C.; Jogi, Krishna; Headey, Derek D.; Joshi, Ramesh; et al. (International Food Policy Research Institute, 2024)
Oral presentations: Linking Agricultural Production Diversity with Household Dietary Diversity: A panel Data Analysis from Rural Bangladesh Taznoore Samina Khanam, Research Fellow, Bangladesh Institute of Development Studies